High‐precision measurements of δ17O and 17Oexcess of NBS19 and NBS18. (27th October 2015) - Barkan, Eugeni; Musan, Israela; Luz, Boaz
Abstract : Rationale: Measurements of oxygen‐17 excess ( 17 Oexcess ) in carbonates have become of great importance. However, to compare results obtained by different laboratories, it is necessary to normalize them to international standards. With this purpose in mind, we measured accurate and high precision δ 17 O and 17 Oexcess values for NBS19 and NBS18, two international standards, for which δ 18 O values are already widely used as the references for carbonates. Methods: The measurements are based on isotopic exchange at steady state between O2 and CO2 over hot platinum sponge at 750°C. Dual‐inlet isotope ratio mass spectrometry (IRMS) measurements of the δ 17 O and δ 18 O values of this O2 allow δ 17 O values of CO2 to be obtained with very high precision (0.01 to 0.03 ‰) and, correspondingly, accurate 17 Oexcess values with a precision of 5 per meg. Results: We measured, for the first time, the δ 17 O values and 17 Oexcess of CO2 liberated from NBS19 at 25°C (39.196 ± 0.026; 20.276 ± 0.015 ‰ and −227 ± 4 per meg, respectively) and NBS18 (17.591 ± 0.041 ‰; 9.253 ± 0.018 ‰ and 3 ± 5 per meg, respectively). The values are given versus VSMOW. Conclusions: Accurate values of δ 17 O and 17 Oexcess of the international standards NBS19‐CO2 and NBS18‐CO2 are now available. The new values should be used for normalization of measured oxygen isotope ratios of carbonates to allow meaningful comparison of results among different laboratories. Copyright © 2015 John Wiley & Sons, Ltd.